The development and implementation of the Nottingham early cognitive and listening links (Early CaLL); A framework designed to support expectation counselling and to monitor the progress, post cochlear implantation, of deaf children with severe (SLD) and profound and multiple learning difficulties (PMLD) and associated complex needs. (2nd January 2020) - Datta, Gill; Durbin, Karen; Odell, Amanda; Ramirez-Inscoe, Jayne; Twomey, Tracey
Abstract : Objectives: Appropriate outcome measures are required for deaf children with severe (SLD) and profound and multiple learning difficulties (PMLD). This paper describes the development and structure of the Nottingham Early CaLL Framework and via a series of case-studies, demonstrates its effectiveness in tracking progress over time. Methods : The materials were developed in-house in 2011–2012 and refined through the exploration of established approaches in health and education, an inter-rater reliability study and an extended pilot of the draft materials. Results : The Framework quantifies the long term benefit of cochlear implantation by recording the amount of functional sound processor use achieved, alongside incremental changes in auditory behaviours, in the context of cognition, interaction and communication development. The case-studies demonstrate how it can provide evidence of measurable changes and help to explain some of the underlying reasons for the range of long-term outcomes. Discussion : Within this population, the key predictive, within-child factors of post cochlear implant listening and spoken language outcomes, are an individual's cognitive and physical capacities and their engagement in social communication. Conclusion : The Early CaLL Framework supports expectation counselling and decision-making in the assessment phase and post cochlear implantation provides monitoring tool, which encourages collaboration between families and professionals.